Pediatric tracheotomy: Indications and decannulation outcomes. (20th February 2014) - Funamura, Jamie L.; Durbin‐Johnson, Blythe; Tollefson, Travis T.; Harrison, Jeanette; Senders, Craig W.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The objective of this study was to determine if there are differences in decannulation rates and duration of cannulation between pediatric patients undergoing tracheotomy for different indications. Study Design Retrospective chart review. Methods Medical records for pediatric patients (age 0–18 years) undergoing tracheotomy between January 1, 2003, and May 31, 2012, were retrospectively reviewed. Patients were assigned an indication for tracheotomy from five categories: neurological, cardiopulmonary, upper airway obstruction, craniofacial anomalies, and maxillofacial/laryngotracheal trauma. Results Initial chart review identified 124 patients, 113 for whom complete data was available. Of these patients, the indications for tracheotomy were cardiopulmonary disease in 24 (21.2%), craniofacial anomalies in 12 (10.6%), neurological impairment in 44 (38.9%), traumatic injury in 11 (9.7%), and upper airway obstruction in 22 (19.5%). The time to decannulation was shorter for trauma patients compared to cardiopulmonary (P = 0.044) and neurological patients (P = 0.001). A total of 32 (31.9%) patients were decannulated during the study period, with a higher rate in trauma patients (72.7%) and a lower rate in those with upper airway obstruction (36.4%) than would be expected under homogeneity. Of the 32 patients who were decannulated, 11 (30.6%) were decannulated during the same hospitalization in which the tracheotomy was performed. Conclusion This study demonstrates a difference in overall decannulation rates and a shorter time to decannulation in children undergoing tracheotomy for maxillofacial and laryngotracheal trauma compared to cardiopulmonary and neurological indications. Level of Evidence 4. Laryngoscope, 124:1952–1958, 2014